Simulasi PhET Sebagai Laboratorium Virtual dalam Peningkatan Pemahaman Konsep Fisika Siswa SMAN 3 Painan, Pesisir Selatan - Sri Oktamuliani; Betta Centaury; Salim Muhaimin; Afdal Afdal; Rico Adrial; Muldarisnur Muldarisnur; Afdhal Muttaqin; Zulfi Zulfi; Alimin Mahyudin (Warta Pengabdian Andalas, 2021)
Learning media is an essential aspect in explaining or visualizing fundamentals of physics that are difficult to understand. Learning media with simulations is increasingly beneficial when Indonesia is affected by the COVID-19 pandemic, which requires distance learning or online education to be implemented. The community service of the Physics Department of Andalas University aimed to introduce PhET simulations as a virtual laboratory to improve understanding of Physics fundamentals for students at SMAN 3 Painan, Kab. Pesisir Selatan, West Sumatra in 2021. Preparation of community service begins with preparing a practicum module from a simulation of the topic of Physics. The assessment of increasing students' understanding of simulation is carried out in Hooke's law module. The number of participating students was grouped into control students (10 people) and students with Hooke's law PhET simulation training (10 people) by giving pre-test and post-test treatments. The t-test analysis shows that the control group and the PhET simulation produced the same output (p = 0.05) at pre-test. It means that the abilities of both groups were the same during the pre-test. In contrast to the post-test case, the PhET simulation group produced higher output than the control group. It means that students' ability in Hooke's law simulation PhET training experienced a significant increase in understanding (p < 0.05). This community service activity can help improve students' understanding to learn the physics fundamentals in SMAN 3 Painan.